2001
DOI: 10.1080/14015430127771
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness of stuttering in Shanghai, China

Abstract: This study reports the results of an investigation of knowledge and public awareness of stuttering among laypersons in Shanghai, China. A total number of 1968 respondents answered a questionnaire including questions about prevalence, onset, gender distribution and occurrence in different cultures, cause, treatment, intelligence and heredity of stuttering. Stuttering appears to be a disorder that most people in the Shanghai area are familiar with, and for several aspects a considerable number of respondents hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 4 publications
2
12
1
Order By: Relevance
“…Findings that respondents' educational attainment is associated with more accurate beliefs were consistent with studies in the US and beyond (de Britto Pereira et al, 2008). Relative to age, previous evidence was based on samples outside the US, with some indicating that older individuals have more inaccurate beliefs about stuttering (de Britto Pereira et al, 2008;Ming et al, 2001;Van Borsel et al, 1999). However, one study indicated older individuals' beliefs are more accurate than younger respondents (Al-Khaledi et al, 2009).…”
Section: Associations With Age Education and Beliefs About Pwssupporting
confidence: 72%
See 3 more Smart Citations
“…Findings that respondents' educational attainment is associated with more accurate beliefs were consistent with studies in the US and beyond (de Britto Pereira et al, 2008). Relative to age, previous evidence was based on samples outside the US, with some indicating that older individuals have more inaccurate beliefs about stuttering (de Britto Pereira et al, 2008;Ming et al, 2001;Van Borsel et al, 1999). However, one study indicated older individuals' beliefs are more accurate than younger respondents (Al-Khaledi et al, 2009).…”
Section: Associations With Age Education and Beliefs About Pwssupporting
confidence: 72%
“…Finally, because our findings regarding the association between beliefs about PWS and other variables in the model, including gender, age, and familiarity with PWS, were in conflict with some previous findings (de Britto Pereira et al, 2008;Ming et al, 2001), it would seem that these associations and their underlying mechanisms warrant further study.…”
Section: Limitations and Future Directionscontrasting
confidence: 71%
See 2 more Smart Citations
“…21 However, later research reported less negative attitudes for adult women than men. 22 Some studies 23,24 inspected individual items in the questionnaire and found that for some items men had more positive perceptions of those who stutter than women, but the reverse was observed for other items. In one study, self-disclosure of stuttering was affected by sex bias by the observers.…”
Section: Introductionmentioning
confidence: 99%